2018
DOI: 10.3390/catal8120580
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-Phase (2H and 1T) MoS2 Catalyst for a Highly Efficient and Stable Si Photocathode

Abstract: We describe the direct formation of mixed-phase (1T and 2H) MoS2 layers on Si as a photocathode via atomic layer deposition (ALD) for application in the photoelectrochemical (PEC) reduction of water to hydrogen. Without typical series-metal interfaces between Si and MoS2, our p-Si/SiOx/MoS2 photocathode showed efficient and stable operation in hydrogen evolution reactions (HERs). The resulting performance could be explained by spatially genuine device architectures in three dimensions (i.e., laterally homo and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 56 publications
1
25
0
Order By: Relevance
“…Deconvoluted S 2p XPS are summarized in Table S3 of supporting information. Deconvoluted XPS spectrum of Mo and S for NMS2 and NMS3 confirmed the presence of both 1T and 2H phases . The Mo 3p XPS profile of MoS 2 and NMSd are shown in Figure (a–d).…”
Section: Resultsmentioning
confidence: 75%
“…Deconvoluted S 2p XPS are summarized in Table S3 of supporting information. Deconvoluted XPS spectrum of Mo and S for NMS2 and NMS3 confirmed the presence of both 1T and 2H phases . The Mo 3p XPS profile of MoS 2 and NMSd are shown in Figure (a–d).…”
Section: Resultsmentioning
confidence: 75%
“…It was also stable during 10,000 s during PEC operation [81]. Joe et al, found that the mixed-phase MoS 2 could improve the Si photocathode for PEC WS by regulating the systems impedance [53].…”
Section: Si/si/transition Metal (Di)chalcogenides [Tm(d)c] Photocathodementioning
confidence: 97%
“…Note also that there exists Fermi-level depinning (FLDP ox ) by the presence of oxide interfaces, e.g., SiO x between the metal and Si [129]. We also suspect that the presence of the continuously mixed phases would lead to ideal band edge pinning, indicative of facilitated charge transfer in the catalyst layer [53], reducing R cat . Moreover, the catalysts with a lateral dimension less than the depletion width and with different work function values form inhomogeneous junctions to the absorber.…”
Section: Toward Multi-phase Tm(d)c Co-catalysts On Simentioning
confidence: 98%
See 2 more Smart Citations